Sistem Pembelajaran Hukum Baca Al-Qur’an Menggunakan Algoritma LPC dan KNN - Hafizh Achmad Dinan; Youllia Indrawaty N; Kurnia Ramadhan Putra (Systemic: Information System and Informatics Journal, 2020)
A Muslim must be able to read the verses of the Qur’an properly as taught by the Prophet, Muhammad. Reading the Qur'an in accordance with tajwid is obligatory for every Muslim, if someone reads the Qur'an without using tajwid, the law is sinful. The development of the application of learning the Tajwid of Qur’an is aimed at helping a Muslim to be good at reading the Qur’an that is good and right.Al-Fatihah is uses in this application. Learning the Tajwid of Qur’an Application is using Linear Predictive Coding (LPC) method as sound feature extraction and K-Nearest Neigbor as matching with training data. For testing the pronunciation of the 1st verse obtained data accuracy of 83.3%, the 2nd verse is 86.7%, the 3rd verse is 85%, the 4th verse is 80%, the 5th verse is 88.3%, the 6th verse is 93.3%.